Art nouveau tiles - Lemmen, Hans van.; Verbrugge, B. D. (Bart D.) (New York : Rizzoli International Publications, 1999)
At the turn of the century, Art Nouveau-- characterized by richly ornamental, curvilinear design-- held sway as the international style in art, architecture, and decorative arts, including the production of tiles. This is the first book to examine Art Nouveau tiles from all over Europe as well as the United States, and an essential volume for the collector and interior designer, featuring 200 stunning color photographs of these ceramic treasures.The authors explore various techniques and processes used in the creation of Art Nouveau tiles, from hand-painting and mosaic work to terracotta and faience, as well as the history of tile production and the architectural application of tiles in Europe, Russia, and America from the mid-nineteenth century to the present day. The book traces the roots of Art Nouveau to the British Arts and Crafts movement, which produced tile work by such artists as William Morris, William De Morgan, and Christopher Dresser. Following this, the wide variety of Art Nouveau tiles across northern and Central Europe is surveyed in detail: in Belgium, France, Germany, Holland, Austria, the Czech Republic, and Hungary. Separate chapters are also devoted to Spain and Portugal, and the unique tradition of American tile-making-- highlighting the work of important designers, artists, architects, and manufacturers. To conclude their survey, the authors look at how elements of Art Nouveau were absorbed into Art Deco after World War I, and the revival of Art Nouveau styles of tile-making in the 1980s and 1990s. A special section for collectors discusses the significance of tile motifs, and offers information about marks on tile backs and advice on acquisition, display, restoration, and repair.
Arts and Crafts Inspirations -- The Rise of Art Nouveau -- Northern Europe -- Central Europe -- Southern Extravaganza -- New World Experiments -- Art Nouveau and Beyond -- Collecting Art Nouveau Tiles.
Includes bibliographical references and index.
Keywords: Decoration and ornament -- Art nouveau; Tiles; Decoration and ornament -- Art nouveau; Tiles; Tegels; Art nouveau